2022
DOI: 10.4209/aaqr.210170
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and Ambient Air Pollution in Chennai, India during COVID-19 Lockdown: An Affordable Sensors Study

Abstract: The Tamil Nadu Air Pollution and Health Effects study (TAPHE-2) aims to evaluate the relationship between air pollution and birth outcome in a rural-urban cohort of 300 pregnant women. Due to COVID-19 related lockdowns, some TAPHE-2 activities were delayed; however, continuous indoor and outdoor air quality data were collected in and around Chennai, India. We report here the impact of graded COVID-19 lockdown on indoor particulate matter (PM2.5 and PM10) levels based on calibrated data from affordable real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…In addition, the SD card in Atmos stores data as a backup. More details on Atmos and the Plantower PMS7003 can be found elsewhere. , …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the SD card in Atmos stores data as a backup. More details on Atmos and the Plantower PMS7003 can be found elsewhere. , …”
Section: Methodsmentioning
confidence: 99%
“…Recently there is increased interest in understanding LCS performance in the Global South to fill major monitoring gaps (Bai et al, 2020;Jha et al, 2021;Malyan et al, 2023;McFarlane et al, 2021;Puttaswamy et al, 2022;Sreekanth et al, 2022;Zheng et al, 2018Zheng et al, , 2019. In North India, Zheng et al (2018) deployed Plantower models in Kanpur, Uttar Pradesh, for 90 days and found multilinear regression improved Plantower performance, albeit with significant error for hourly data.…”
Section: Introductionmentioning
confidence: 99%
“…In North India, Zheng et al (2018) deployed Plantower models in Kanpur, Uttar Pradesh, for 90 days and found multilinear regression improved Plantower performance, albeit with significant error for hourly data. In South India, Puttaswamy et al (2022) calibrated Plantower units for 68-days in Chennai and found a multilinear regression approach reduced uncertainty to within 15% and 18% for PM 2.5 and PM 10 respectively. LCS studies in India report the importance of climate and emissions variability on aerosol characteristics and advise future deployments to test calibration algorithms across longer timelines (Malyan et al, 2023;Puttaswamy et al, 2022;Sreekanth et al, 2022;Zheng et al, 2018Zheng et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the number of vehicles on highways in the Metropolitan Region of São Paulo (MRSP), Brazil, decreased by 50% compared to 2019, and air quality improved significantly (Perez-Martinez et al 2022). During the outbreak lockdown, both indoor and ambient PM levels in Chennai, India, were significantly reduced (Puttaswamy et al 2022). Changes in anthropogenic emissions in Hubei Province, China, during the COVID-19 outbreak resulted in a decrease in PM 2.5 concentration levels of about 33.3% compared to the same period in 2019, while changes in meteorological conditions increased PM 2.5 concentrations by about 8.8% (Liu et al 2022).…”
Section: Introductionmentioning
confidence: 99%